Hygiene status of food contact surfaces in public school canteens in the city of Novi Sad, Serbia - Popović, Milka; Baltić, Milan Ž; Gusman, Vera; Anđelković, Radivoje; Velicki, Radmila; Bjelanović, Jelena; Mitrović, Radmila; Janjić, Jelena (Vojnosanitetski pregled, 2022)
Background/Aim. Establishing a food safety control system is extremely important in preventing diseases associated with foodborne pathogens. The aim of this study was to examine the hygiene status of food contact surfaces and the application of good hygiene practices by food handlers in school canteens. Methods. A total of 10,366 swabs were taken from food contact surfaces, including food handler’s hands from public school canteens in Novi Sad, Serbia, over ten years (2008–2017), covering voluntary good hygiene practices and obligatory Hazard Analysis Critical Control Points (HACCP) implementation periods. Results. Statistically significant differences (p < 0.05) in aerobic colony counts (ACCs) on surfaces between two examined periods were found. A general positive trend regarding the reduction of microbial contamination of food contact surfaces was observed. The percentage of surfaces swabs with ACCs above 2.48 log CFU/cm2 significantly decreased (R2 = 0.453) during the study period, and the percentage of coagulase-positive Staphylococcus in the swabs also decreased, but not significantly (R2 = 0.264), and average annual Enterobacteriaceae counts above the established limit values on surfaces significantly decreased (R2 = 0.442) over the years. A significantly higher (p < 0.05) percentage of workers’ hands harbored ACCs, coagulase-positive Staphylococcus, and Enterobacteriaceae above the established limits than the equipment or work surfaces. Conclusion. The results obtained showed the proper implementation of good hygiene practices concerning food contact surfaces, but the implementation of good personal hygiene practices needs enhanced supervision.